Community adaptation to climate in open spaces of the semi-arid region of Northern Nigeria - Muhammad Gidado, Usman; Maulan, Suhardi; Maimuna, Saleh Bala (IFLA Africa, 2022)
Open areas are used for socio-cultural displays, recreation, and religious festivities in semi-arid areas. Desertification has severe impacts not just on agricultural land, but also on open spaces. The menace of land degradation necessitates the development of adaptation strategies by local communities as coping mechanisms. However, adaptation efforts will be difficult to sustain if they are not supported by viable long-term adaptation plans or structures. Through field observation and in-depth interviews with community heads of five communities in the Batagarawa local government area of Katsina State and the use of ATLAS Ti for data processing, Indigenous knowledge was shown to be critical in the development of several adaptation options and strategies for community open spaces. The study recommends the establishment of an adaptation framework for the sustainability of open spaces by incorporating indigenous knowledge. The findings of this study will aid in developing contextual policies that consider local nuances.